Resolving tricky nodes in the tree of life through amino acid recoding - Mattia Giacomelli; Maria Eleonora Rossi; Jesus Lozano-Fernandez; Roberto Feuda; Davide Pisani (iScience, 2022)
Summary: Genomic data allowed a detailed resolution of the Tree of Life, but “tricky nodes” such as the root of the animals remain unresolved. Genome-scale datasets are heterogeneous as genes and species are exposed to different pressures, and this can negatively impacts phylogenetic accuracy. We use simulated genomic-scale datasets and show that recoding amino acid data improves accuracy when the model does not account for the compositional heterogeneity of the amino acid alignment. We apply our findings to three datasets addressing the root of the animal tree, where the debate centers on whether sponges (Porifera) or comb jellies (Ctenophora) represent the sister of all other animals. We show that results from empirical data follow predictions from simulations and suggest that, at the least in phylogenies inferred from amino acid sequences, a placement of the ctenophores as sister to all the other animals is best explained as a tree reconstruction artifact.